THE EFFECTIVENESS OF ENGLISH SONG "DRIVER LICENSE" TO IMPROVE STUDENTS' SPEAKING SKILL - Nandita Nuraini; Yanti Rusmiyati (Jurnal Dedikasi Pendidikan, 2022)
The purpose of this research are  (1) to identify the extent of students’ speaking skill and to help student improves their speaking skill by using an English song  and (2) to identify the strength and weaknesses using English song in learning speaking. Speaking is one of the some skills among listening, writing, and reading. This research used descriptive quantitative research design. Where the writer describes and analyzes the students’ error speaking skill. Learning English through songs is one of the most effective ways to help students concentrate on the lessons. In any case, the teacher ought to not forget the most reason that utilizing songs in teaching English is as it were the device in arranged to point the students in English’s classroom. In short, the writer trusts that utilizing tunes will be successful way for students’ speaking skill. This is evidenced by the pre-test and cycle II scores, it can be seen that there is an increase of 11, 16 from the initial score.